Review of oximes in the antidotal treatment of poisoning by organophosphorus nerve agents - Kassa, J (Journal of toxicology. Clinical toxicology, 2002)
The cholinesterase-inhibiting organophosphorus compounds referred to as nerve agents (soman, sarin, tabun, GF agent, and VX) are particularly toxic and are considered to be among the most dangerous chemical warfare agents. Included in antidotal medical countermeasures are oximes to reactivate the inhibited cholinesterase. Much experimental work has been done to better understand the properties of the oxime antidotal candidates including the currently available pralidoxime and obidoxime, the H oximes HI-6 and Hlö-7, and methoxime. There is no single, broad-spectrum oxime suitablefor the antidotal treatment of poisoning with all organophosphorus agents. If more than one oxime is available, the choice depends primarily on the identity of the responsible organophosphorus compound. The H oximes appear to be very promising antidotes against nerve agents because they are able to protect experimental animals from toxic effects and improve survival of animals poisoned with supralethal doses. They appear more effective against nerve agent poisoning than the currently used oximes pralidoxime and obidoxime, especially in the case of soman poisoning. On the other hand, pralidoxime and especially obidoxime seem sufficiently effective to treat poisonings with organophosphorus insecticides that have relatively less toxicity than nerve agents.
Keywords: Animals; Humans; Poisoning; Chemical Warfare Agents; lidé; antidota; zvířata; Oximes; chemické bojové látky; otrava; Organophosphate Poisoning; Antidotes; organofosforové sloučeniny; Organophosphorus Compounds; oximy; otrava organofosfáty